(untitled) - Cowper, Anna (Harlow, England, 2013)
English for International Tourism is a three-level series designed to meet the English-language needs of professionals working in the tourism industry and students of tourism in further education. The course includes authentic material taken from the world’s best-loved guidebooks, Dorling Kindersley’s Eyewitness Travel Guides which explore some of the world's top tourist destinations. English for International Tourism Workbook with key offers a wide variety of practice and review exercices and covers all of the language areas studied in the unit. With audio CD including all the audio material of the workbook.
Keywords: Tourism,English language,English languages,Tiếng Anh,Tiếng Anh,Du lịch; Terminology,Problems, exercises, etc.,Textbooks for foreign speakers,Câu hỏi và bài tập,Sách giáo khoa cho người nước ngoài,Thuật ngữ